Freud’s transference - Monteiro, Elisabete Aparecida (Clinical Styles. The Journal on the vicissitudes of childhood, 1999)
The psychoanalysis has developed itself due to the negative effects of the transference (to the resistance), what means that the history of the concept of transference is the history of the psychoanalysis itself. The psychoanalytical theory, otherwise, is the result of Freud's psychic "movement", therefore, of its transferences. Thus, understanding the concept of transference means an incursion into Freud's affective life, into his relationships with masters, friends and master-friends.